1978
DOI: 10.1111/j.1365-2761.1978.tb00033.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Herpesvirus scophthalmi infection of turbot Scophthalmus maximus (L.) ultrastructural observations

Abstract: Recent heavy mortalities amongst 0+ group turbot at a fish farm were found to be associated with a heriDes-type viral itifection of the epithelia of the skin and gills. The morphology o.f the virus is described with ultrastructural observations on its morphogenesis and release from infected cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0
1

Year Published

1979
1979
2012
2012

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 21 publications
4
9
0
1
Order By: Relevance
“…Scale bar = 100 nm. Herpesviruses in fish are typically unenveloped in the nucleus and enveloped in the cytoplasm (Buchanan & Madeley 1978, Anders 1989, Shchelkunov et al 1992, like those we observed in rainbow smelt tumors. The herpesvirus capsids in the nucleus were similar in size and morphology to those found in European smelt (Anders & Moller 1985, Wolf 1988, Anders 1989), but the cytoplasmic virions did not have tail-like extensions like some in European smelt.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Scale bar = 100 nm. Herpesviruses in fish are typically unenveloped in the nucleus and enveloped in the cytoplasm (Buchanan & Madeley 1978, Anders 1989, Shchelkunov et al 1992, like those we observed in rainbow smelt tumors. The herpesvirus capsids in the nucleus were similar in size and morphology to those found in European smelt (Anders & Moller 1985, Wolf 1988, Anders 1989), but the cytoplasmic virions did not have tail-like extensions like some in European smelt.…”
Section: Discussionsupporting
confidence: 75%
“…In most cases herpesviruses are thought to acquire their envelope layers at the inner nuclear membrane (Buchanan & Richards 1982), and to be released from the cell through cytoplasmic vacuoles (Buchanan & Madeley 1978). In our study, many of these vacuoles were apparently produced by an enlarged Golgi body.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Twelve were associated with epidermal tumours including OMV and CHV, 1 with spawning papillomatosis of smelt ( Fig. 3c to f ) , 3 with so-called 'giant cell hyperplasias ' (McArn et al 1978, McCain et al 1979, Yamamoto et al 1984, Leibovitz & Lebouitz 1985, and 1 with giant cell formation within a nonaltered epidermis (Buchanan & Madeley 1978). The other 5 comprise the 2 salmonid herpesviruses Herpesvirus salmonis (Wolf & Taylor 1975, Hedrick et al 1986 and NeVTA (Nerka Virus in Towada Lake Akita and Aomori Prefecture; Sano 1976), a herpesvirus of European and Japanese eels (Sano et al 1988), channel catfish virus (Fijan et al 1970), and a recently described herpesvirus from white sturgeon (Hedrick et al 1991).…”
Section: Viruses Visualized By Electron Microscopymentioning
confidence: 99%
“…The only DNA virus, the herpes virus scophthalmi (Buchanam and Madeley, 1978), was found using electron microscopy.…”
Section: Introductionmentioning
confidence: 99%